AdaptME toolkit : adaptation monitoring and evaluation - Pringle, P (UKCIP, 2011)
Organisations that have undertaken adaptation activities now face the challenge of evaluating what worked, what didn’t, how and why. This toolkit responds to a growing demand for practical support in evaluating adaptation progress and performance. AdaptME will help you to think through some of the factors that can make an evaluation of adaptation activities inherently challenging, and equip you to design a robust evaluation. You will be able to ‘tweak’ a single part of your evaluation design or use multiple tools to build a new approach – that is for you to decide!